UTILIZATION OF MANGO WASTE FOR BIOETHANOL PRODUCTION USING ASPERGILLUS NIGER AND SACCHAROMYCETES CEREVISAE: A PILOT-SCALE STUDY - Selvia Sarungu’; Sitompul Afrida; Markus Lumbaa (PETROGAS: Journal of Energy and Technology, 2021)
The modern life is highly dependent on energy including for fuel, electricity, and industry. Fossil fuels are the main of energy source is used. However, negative environmental effects are needed to be considered. Biomass energy using waste or plant matter produces a lower level of greenhouse gas emissions than fossil fuels. Through this study, we attempt to use mango waste to produce bioethanol. This source is cellulosic material which is abundant in traditional markets, especially when the peak of harvest season comes. We treated the mango waste in pilot-scale experiment with three different ways using alcohol percentage as an indicator of the alcohol production. Monoculture fermentation of Saccharomycetes cerevisiae produced the highest bio-ethanol percentage (83% v/v). A slightly higher in alcohol percentage (79% v/v) was achieved by coculture fermentation of Aspergillus niger and S. cerevisiae. The lowest result was obtained in fermentation of A. niger was followed by the addition of S. cerevisiae (70% v/v). These results indicate that monoculture fermentation of mango waste gives the best results. This research may be useful in production of bio-ethanol for industrial scale.